The influence of brand image on purchase intention in social commerce TikTok Shop: The role of trust - Saktiawan, Bimo; Permatasari, Harnung Indah; Wulandari, Trisninik Ratih (Sebelas Maret Business Review, 2023)
People are starting to change their habits, especially after the Covid-19 pandemic, which made them prefer shopping online. Many online shopping platforms can be used by consumers, including social media as well as e-commerce or the social commerce term TikTok Shop. The TikTok application has great potential in the e-commerce sector, including the marketing industry and online shopping media in the form of short videos. On the other hand, TikTok can provide a positive value to the brand image of a product. If the product has a positive brand image, the impact will be that people will trust and know the product well. Besides the brand image, consumer purchase intention is also based on trust. The problem is consumer trust in TikTok as a social media-based online shopping tool is still being debated. This study aims to prove the effect of brand image mediated by customer trust on purchase intention in the social commerce TikTok Shop. This research method is quantitative, and the data used is primary data from an online survey via LimeSurvey. The total number of respondents is 333 people who are spread throughout Indonesia. Next, the collected data was analyzed by SEM on SmartPLS. The results of the study show that brand image has a significant effect on customer trust and purchase intention.